Florestas comestíveis, o potencial da biodiversidade alimentar nativa na Floresta Nacional de Ipanema - Guilherme, André (Universidade Federal de São Carlos, 2022)
Currently 50.104 of 381.959 accepted plant species, 13.11% of the world flora, are Brazilian, many of them with real or potencial value for agriculture and food. Also known as food biodiversity, numerous of these negletcted and underutilized species may have important characteristics for the economy, nutrition, food, and could also be strategic in the face of a range of global environmental changes. However, local varieties and species of food plants are threatened around the world, representing serious risk to global food security. On the other hand, a large part of this biodiversity can be found in protected areas, special places which are maneged for in situ conservations purpouse. In that connection this study explore the idea that protected areas like Ipanema National Forests (Flona de Ipanema) can shelter withing their territories a litlle-explore food biodiversity. While a sustainable-use area the Flona de Ipanema is afforting protection to valuable areas of Atlantic Rainforest and Cerrado and support a high biodiversity. Therefore, the objectiv of this study are (1) make a food biodiversity inventory of Brazilian flora in Flona de Ipanema, evidencing its alimentary value and strategic importance for environmental conservation, and (2) investigate the perception of visitors about the ecossistem provisioning services provide by the protected area. The results are presented in two chapters. The first chapter show the presence of an almost unnoticed food biodiversity, represented by 22 species, and seeks demonstrate their current and potential use, and links due to multiple-use, to evironmental, social and economic aspects, benefiting both the Flona de Ipanema and the surrounding population. The second charpter demonstrate that the ecossistem provisioning (food) services is not percieved by visitors, a fact that could be associeted to the main emphasis of public-use programs, that are historically founded in cultural services activities perceived by 89%, followed by supporting services, 10%, with no mention of regulating services. The informations surveyed in this study also make possible to create tools to enable the native food biodiversity conservation, sustainable use and income generation, encrease the capacity to montitoring, management and use of Flona de Ipanema resources. Fourthermore, there is the possibility to use the first charpter results to design new activities and improve the visitor experience.
Edible forests, the potential of brazilian food biodiversity in the Ipanema National Forest
Keywords: Biodiversidade alimentar; Unidades de Conservação; Serviços Ecossistêmicos; Flona; Morro Araçoiaba; Food biodiversity; Protected areas; Ecosystem Services; Araçoiaba Hill; CIENCIAS BIOLOGICAS::BOTANICA::BOTANICA APLICADA; CIENCIAS BIOLOGICAS::BIOLOGIA GERAL; CIENCIAS BIOLOGICAS::BOTANICA; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE AREAS SILVESTRES; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::RECUPERACAO DE AREAS DEGRADADAS; OUTROS::CIENCIAS